ANTIFUNGAL ACTIVITY OF ESSENTIAL OILS SOME PLANTS IN ACEH PROVINCE AGAINST Candida albican - Binawati Ginting (Universitas Syiah Kuala, 2012)
It has been tested antifungal essential oils from the leaves of Wedelia biflora, leaves of Citrus hystrix Dc, leaves of Ocimum basilicum L., and flower Caesalpinia pulcherima L. at concentrations of 10, 5 and 1% against C. albicans. using the Kirby-Bower. The antifungal activity of essential oils the leaves of Citrus hystrix Dc with a concentration of 10%, 5% and 1% respectively show the average of the inhibition zone by 24.5 mm, 23 mm and 10 mm. Essential oils leaves of Ocimum basilicum L at concentrations of 10%, 5% and 1% respectively had average inhibition zone of 11.5 mm, 10.5 mm and 6 mm. leaves of Ocimum basilicum L., and flower Caesalpinia pulcherima L showed no inhibition of the C. Albicans.